Food regulation when food safety and healthy diet are in conflict - the case of Baltic herring - Peltola J.; Schalin M. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
Food safety and nutritional issues are most often studied separately. In this paper, we bring the two aspects together. We examine regulators' decision making and policy trade-offs in the EU dioxin regulation. Using an economic model we evaluate how and why the regulation has been designed differently in the Scandinavia than in other EU countries. In our case study of Baltic herring, fish has two important, although contradictory, health aspects. Firstly, it is an important part of a healthy diet but, secondly, it is known to contain carsinogenic dioxins. In the model, the policy maker has a dual-objective: how to account for both food safety and nutrition issues in health regulation. The challenge in policy design is to recognise that when avoiding one risk, even greater risk may appear. In addition, better knowledge on consumer profiles and risk groups is needed to enable more efficient regulation design.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)